Epo and other hematopoietic factors - Juul, Sandra (2007)
The growth factors erythropoietin and granulocyte-colony stimulating factor have hematopoietic and non-hematopoietic functions. Both are used clinically in their recombinant forms. Both also have interesting tissue-protective effects in other organs, which are unrelated to their hematopoietic functions. They have clinical hematopoietic uses in neonatal populations and in experimental non-hematopoietic research, and clinical potential as neuroprotective or tissue-protective agents.